SARS CoV-2 Spike Protein in silico Interaction With ACE2 Receptors From Wild and Domestic Species - Rendon-Marin, Santiago; Martinez-Gutierrez, Marlen; Whittaker, Gary R.; Jaimes, Javier A.; Ruiz-Saenz, Julian (Frontiers in Genetics, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been declared a pandemic by the World Health Organization (WHO) and since its first report it has become a major public health concern. SARS-CoV-2 is closely related to SARS-CoV and SARS-related bat coronaviruses and it has been described to use angiotensin converting enzyme 2 (ACE2) as a receptor. Natural SARS-CoV-2 infection in domestic and wildlife animals, measured by RT-qPCR, has been confirmed in different countries, especially from the Felidae family. In silico analysis of the interaction between the SARS-CoV-2 spike protein and the cellular receptor ACE2 in various animal species have suggested that wild felids and domestic cats could be susceptible to SARS-CoV-2 based on this interaction. Here, we performed a protein-protein molecular docking analysis of SARS-CoV-2 spike protein with the ACE2 receptor from different animals to elucidate the potential of those species as intermediate hosts or susceptible animals for SARS-CoV-2 infection. Compared to human ACE2, we found that ACE2 receptors from domestic cats and tigers could efficiently interact with RBD of SARS CoV-2 Spike protein. However, dog, ferret, and hamster ACE2 receptor interaction with SARS-CoV-2 S protein RBD was not predicted as favorable, demonstrating a potential differentiated susceptibility in the evaluated species.